2017
DOI: 10.3892/ol.2017.7344
|View full text |Cite
|
Sign up to set email alerts
|

Significant expression of CHK1 and p53 in bladder urothelial carcinoma as potential therapeutic targets and prognosis

Abstract: Abstract. Checkpoint kinase 1 (CHK1) and p53 are involved in cell-cycle checkpoint, and cellular response to DNA damage. CHK1 and p53 are overexpressed in bladder urothelial carcinoma (BUC); however, a clear elucidation on their interaction and influence in the progress of BUC is absent. The aim of the present study was to examine the correlation between CHK1 and p53 in BUC, and analyze their value as therapeutic targets and prognostic indicators in BUC. A clinically annotated cohort of 110 patients with BUC w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…TP53 gene variants were reported in our study at similar frequency to TERT gene variants. TP53 genetic variants were reported in SR-SCCUB and conventional UC and were associated with inferior survival outcomes in both histologies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…TP53 gene variants were reported in our study at similar frequency to TERT gene variants. TP53 genetic variants were reported in SR-SCCUB and conventional UC and were associated with inferior survival outcomes in both histologies [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its anti-injury effect, CHEK1 plays an important role in tumor development and apoptosis [ 63 65 ]. Many studies have reported that CCNB1, CCNB2, and CHEK1 were involved in p53 signaling pathway [ 66 68 ]. We found that mRNA levels of three p53 markers including CCNB1, CCNB2, and CHEK1 were significantly upregulated in 20 HCC tumor tissues versus nontumor adjacent tissues by bioinformatics analysis and experimental verification, and their mRNA expression levels were all negatively correlated with HCC patients' survival rates (p<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…DNA damage response is a complex signaling network involving cell cycle checkpoints as well as DNA damage and repair pathways. 43 Herein, 14 molecular changes in gene/protein groups and altered genes/proteins, such as tumor suppressor, antiapoptotic, cyclin, monooxigenase, glycosidase, enzyme binding, transferase, DNA binding, hydrolase, helicase, ribonucleoprotein, exonuclease, endonuclease, and translocase were examined. Meta-analysis for GSTM1 and GSTT1, as well as for transferase and hydrolase groups, showed no significant difference between smokers and non-smokers regarding the damage/polymorphism of these proteins.…”
Section: Uncertain Risk Of Bias Low Risk Of Biasmentioning
confidence: 99%